2019
DOI: 10.3390/su11113084
|View full text |Cite
|
Sign up to set email alerts
|

Human and Natural Impacts on the Water Resources in the Syr Darya River Basin, Central Asia

Abstract: Water resources are increasingly under stress in Central Asia because downstream countries are highly dependent on upstream countries. Water is essential for irrigation and is becoming scarcer due to climate change and human activities. Based on 20 hydrological stations, this study firstly analyzed the annual and seasonal spatial–temporal changes of the river discharges, precipitation, and temperature in the Syr Darya River Basin and then the possible relationships between these factors were detected. Finally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 41 publications
0
27
0
1
Order By: Relevance
“…Projected changes in monthly precipitation and temperature in the Tana sub-basin from 15 GCMs (Global Climate Models-General Circulation Models) were analyzed and it was found that four of the nine GCMs indicated a significant decrease in annual stream flow for the 2080-2100 period [17]. In addition, similarly to other studies on impacts of human interventions on sustainable water use, climate change, unmanaged water abstractions and land use change in the Lake Tana Sub-basin threaten the riverine and lake ecosystems [19,20].…”
Section: Introductionmentioning
confidence: 68%
“…Projected changes in monthly precipitation and temperature in the Tana sub-basin from 15 GCMs (Global Climate Models-General Circulation Models) were analyzed and it was found that four of the nine GCMs indicated a significant decrease in annual stream flow for the 2080-2100 period [17]. In addition, similarly to other studies on impacts of human interventions on sustainable water use, climate change, unmanaged water abstractions and land use change in the Lake Tana Sub-basin threaten the riverine and lake ecosystems [19,20].…”
Section: Introductionmentioning
confidence: 68%
“…Lakes are sensitive to the impacts of climate change, and the impacts include a wide range of negative consequences, such as changes in thermal stratification, an acceleration of the eutrophication which favors periodic proliferation by cyanobacteria in many freshwaters, increased turbidity, and changes in salinity [8][9][10]. In this context, many studies have been carried out regarding the deterioration of water quality due to human influence, and its spatial and temporal variations in rivers or water reservoirs [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven that there has been a significant increase in temperature and in precipitation over Central Asia and the Syrdarya River Basin during the recent decades [15,16]. Moreover, human activities including change in land use (especially the expansion of agricultural land) and dam construction have significantly affected the water supply and water demand patterns, and impact the runoff reductions in this region [17]. Therefore, the water resources of Keles and Arys are very important components of the basin.The water resources of the Keles and Arys rivers' watersheds sustain irrigation systems in the arid region.…”
mentioning
confidence: 99%